Where do Latinas and Latinos earn social science doctorates? - Frank Fernandez (Arizona State University, 2020)
It is a national imperative to increase the percentage of Latinas and Latinos who earn doctorate degrees in the social sciences and who enter into faculty positions. For the purposes of this study, I focus on whether Latinas and Latinos earned their doctorates at the nation's most research-intensive universities because those schools are uniquely equipped to prepare doctoral students for careers in academia. I find that more than 40% of Latinas and Latinos who earned social science doctorates did so at universities with lower research profiles. I also test whether there are relationships between Latinas' and Latino's undergraduate institutions (e.g., community colleges and Hispanic Serving Institutions) and doctoral universities (classified by research-intensity). I did not find a relationship between attending community college and the type of university where a Latina or Latino social scientist earned the PhD. However, I found that Latinas and Latinos who earned baccalaureate degrees from Hispanic Serving Institutions (HSIs) had higher relative risk of earning doctorates from less research-intensive universities. This institutional pathway may be beneficial for increasing the number of Latinas and Latinos who earn social science doctorate degrees; however, it may be problematic for preparing future faculty members. I discuss implications for supporting the Latina-Latino pathway to the PhD.